Healthcare-Associated Infections in Pediatric Patients: A Decade of Experience in an Intensive Care Unit - Martins, Cátia (2025)
Introduction: Healthcare-associated infections are an important cause of morbidity and mortality in the pediatric population and a growing problem in intensive care services. However, limited data are available on these infections in the Portuguese pediatric population. This study aimed to estimate its prevalence rate in a Portuguese pediatric intensive care unit, identifying the most frequent microorganisms and their antibiotic resistance profiles.Methods: A retrospective cohort study was conducted, including patients admitted to a pediatric intensive care unit between January 1, 2014 and December 31, 2023, who were diagnosed with healthcare-associated infections during hospitalization.Results: A total of 248 nosocomial infections were identified, corresponding to a prevalence rate of 6.3%, mostly in infants. Pneumonia (45.2%) and bacteremia (14.5%) were the most frequent infections. Gram-negative bacteria, specifically Escherichia coli, Pseudomonas aeruginosa and Klebsiella pneumoniae, were the most common pathogens. Over the last five years (2019 - 2023), there was a global increase in antibiotic resistance. The prevalence of infections with ESBL-producing bacteria, MRSA and ERC was 8.5%, 1.6%, and 0.4%, respectively, higher in the period from 2019 to 2023. Among 97 screening tests, 45 colonizations were identified in 41 patients: 40 with ESBL and 5 with ERC, with no MRSA colonizations detected. Sepsis occurred in 29.8% of cases, and the mortality rate was 11.7%, with 4.0% directly attributed to healthcare-associated infections. Risk factors for pneumonia included exposure to endotracheal tubes and prolonged invasive ventilation (OR = 2.5; 95% CI, 1.1 to 5.9, p = 0.03; and OR = 1.9; 95% CI, 1.1 to 3.4, p = 0.011; respectively).Conclusion: Implementing effective strategies to prevent and control resistant bacteria is essential to safeguard current therapies, enhance patient safety, and protect public health.